The Vertical Profile Of Dissolved Oxygen in Pinang Dalam Oxbow Lake Buluh China Village Siak Hulu Sub District Kampar District Riau Province - Sinaga, Walmon; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in February-March 2014 in Lake Danau Pinang Dalam. Theresearch aims to understand the vertical profile of Dissolved Oxygen in Pinang Dalam Oxbowlake. The research used survey method. Sample were taken in three stations, namely station 1,station 2 and station 3. Sampling vertical based on depth, at surface, 2,5 secchi disk and in thebottom. The parameter of water quality measured pH, temperature, nitrate, phosphate, depth,transparancy, and dissolved oxygen (DO). The result shown concentration of dissolved oxygenrange 2,04-5,29 mg/L, concentration of nitrate range 0,02-0,34 mg/L and the concentration ofphosphate range 0,01-0,71 mg/L. The value of temperature was 28,50C, depth range of 145-302cm. The value of pH was 5. the parameters of water quality were observed still support theaquatic organisms..Keywords : dissolved oxygen, the vertical profile, Pinang Dalam Oxbow